The relationship between psychological capital and career commitment in teachers - Rizka Awaliah; Tri Muji Ingarianti (Universitas Muhammadiyah Malang, 2024)
When teachers have a high level of psychological capital, it can motivate them to be more proactive, exhibit higher confidence, and achieve better performance. This positive impact, in turn, can lead to strong commitment to their work, career, and the organization they belong to, resulting in the formation of high-quality teaching staff. This research aims to examine the relationship between psychological capital and career commitment among teachers. The participants in this study were 336 teachers. The research utilized a quantitative research model with a correlational method employing the simple linear regression assumption test. The instruments used in this study were the Psychological Capital Questionnaire (PCQ) and Career Commitment Measure (CCM). The results of this study indicate a correlation between two psychological capital dimensions (efficacy and optimism) and three dimensions of career commitment. There is also a relationship between the hope dimension and the identity dimension of career commitment, while the other two dimensions do not have a connection with career commitment dimensions. Additionally, the resilience dimension is also associated with career planning.